It can't hurt to ask; a patient-centered quality of service assessment of health canada's medical cannabis policy and program - Lucas Philippe (BMC, 2012)
Abstract Background In 2001 Health Canada responded to a series of Ontario court decisions by creating the Marihuana Medical Access Division (MMAD) and the Marihuana Medical Access Regulations (MMAR). Although Health Canada has conducted a small number of stakeholder consultations, the federal government has never polled federally authorized cannabis patients. This study is an attempt to learn more about patient needs, challenges and experiences with the MMAD. Methods Launched in the spring of 2007, Quality of Service Assessment of Health Canada's Medical Cannabis Policy and Program pairs a 50 question online survey addressing the personal experiences of patients in the federal cannabis program with 25 semi-guided interviews. Data gathering for this study took place from April 2007 to Jan. 2008, eventually garnering survey responses from 100 federally-authorized users, which at the time represented about 5% of the patients enrolled in Health Canada's program. This paper presents the results of the survey portion of the study. Results 8% of respondents report getting their cannabis from Health Canada, while 66% grow it for themselves. >50% report that they frequent compassion clubs or dispensaries, which remain illegal and unregulated in Canada. 81% of patients would chose certified organic methods of cultivation; >90% state that not all strains are equally effective at relieving symptoms, and 97% would prefer to obtain cannabis from a source where multiple strains are available. Of the 48 patients polled that had tried the Health Canada cannabis supply, >75% rank it as either "1" or "2" on a scale of 1-10 (with "1" being "very poor", and 10 being "excellent"). Discussion 72% of respondents report they are either "somewhat" or "totally unsatisfied" with Canada's medical cannabis program. These survey results and relevant court decisions suggest that the MMAR are not meeting the needs of most of the nation's medical cannabis patient community. It is hoped this research will help inform policy changes that will better address the needs of Canada's critically and chronically ill medical cannabis patient population, including the integration of community-based dispensaries into this novel healthcare delivery model.